The Enthymemes of St. Petersburg University Art Studies during the 1870s and 1880s - Evsevyev, Mikhail I.; Sokhor, Tatyana E. (Actual Problems of Theory and History of Art, 2020)
The paper examines an early period in the development of art history studies at Saint-Petersburg University and the foundation of a special Department dedicated to it in 1874. Adrian Prakhov, a beginer artist and university graduate, who honed his education with a four-year trip around Europe, later became the first professor of the Department. As it became evident even before the establishment of the Department, an alternative figure to Prakhov was Russian professional art critic Vladimir Stasov. Their rivalry made it possible to compare and specify the peculiar features of art history studies at the University in the last quarter of the19th century, including its possible orientation to the Classical European art of the ancient world (Prakhov) or to Russian art (Stasov).Thanks to Stasov’s interest in Prakhov’s activity as an applicant for the position of a professor and later a professor of the Department of Art History, we know some events of the early period of its existence,including the date of the first lecture which is considered to be the birthday of the Department — 22 February (6 March) 1874.
Keywords: Adrian Prakhov; Vladimir Stasov; Imperial Academy of arts; St. Petersburg University; Department of Art History; memoirs; University Charter; art history education